Outcomes of Endovascular Intervention for Salvage of Failing Hemodialysis Access - Karundeng, Billy; Tjandra, Djony; Sumangkut, Richard; Winarto, Michael D. (Medical Scope Journal, 2025)
Abstract: Chronic kidney disease (CKD) is a worldwide public health problem. Hemodialysis accesses are prone to failure due to thrombosis and stenosis over the anastomosis or outflow vein. This study aimed to obtain the outcomes of endovascular intervention for salvage of failing hemodialysis access. This was a retrospective and descriptibe study. Data were collected from all patients who underwent endovascular intervention for failing hemodialysis access starting from January 2021 – June 2023 at Prof. Dr. R. D. Kandou Hospital, Manado. The results showed that 136 subjects were included in this study. The highest comorbidities were found in patients with a history of hypertension (52.9%). The most common arteriovenous fistulas (AVF) hemodialysis access was at the brachiocephalic location (75.7%). The most frequent cause of access dysfunction was simple stenosis (64.7%). Pseudoaneurysm was occurred in two subjects (1.4%), and ruptured outflow vein was occurred in one subject (0.7%). The patency rate at three months was 77.6%, but the primary patency rate would decrease to less than 50% over six months. Endovascular intervention in the form of balloon angioplasty is currently the main line of choice in dealing with problematic AVFs in principle what is being done is to intraluminaly dilate the narrowed or blocked lumen of the outflow vein. The complication rate from the procedure performed was 2.2% where in two patients a pseudoaneurysm occurred at the puncture site, namely the brachial artery and the radial artery then another patient had rupture of the AVFs outflow vein, therefore, an additional procedure was performed to close the AVFs with ligation. In conclusion, endovascular intervention for failing hemodialysis access has good results, but the primary patency rate will decrease to less than 50% over six months. Keywords: chronic kidney disease; hemodialysis access; endovascular intervention